A Case Study of Initiating Mentoring in an Urban Charter School - Mascelli, Meghan Smith (The George Washington University, 2016)
A Case Study of Initiating Mentoring in an Urban Charter School Most states exempt public charter schools from state policy that regulates the mentorship of new teachers. Regardless, there are charter systems that develop teacher mentor programs on their own. These system-created programs can create a dichotomy between charter expectation and mentor/mentee experience. Utilizing a case study approach, this dissertation offers a unique view into this phenomenon, by examining the inaugural year of a mid-sized urban charter system’s effort to design and implement a teacher mentoring support program. Data include interviews with 15 teachers (paired and unmatched mentors and mentees) and administrators, meeting observations, and reviews of program documents and artifacts. Findings note challenges related to support, guidance, and expectations, in addition to a cautious optimism about future charter mentor endeavors. Miller’s (1976) Relational cultural theory was used as a theoretical lens to explore teacher experiences in mentoring. The results of this study enhance understanding of urban public charter school teachers engaged in the mentoring process by: (a) identifying clear mentoring program expectations, administrative involvement, and professional development as influential factors in mentoring relationships; (b) recognizing mentor experience, shared subject matter of mentor and mentee, and ability to meet in person as powerful predictors of mentor relationship success; and (c) illustrating how school context can and does affect the mentoring process in an urban public charter school. Keywords: mentoring, charter schools, beginning teachers, teacher development